Modeling unsteady filtration performance of pleated filter - Feng, Zhuangbo; Long, Zhengwei (Aerosol science and technology, 2016)
The dust loading has a significant influence on the transient performance of air filters. This study developed two models based on the Lagrangian and Eulerian methods to simulate the unsteady filtration process in the pleated filter. The flow field through the filter was calculated by solving the Navier-Stokes equation with the DES-SA turbulence model. The filter media and the cake layer were modeled as the porous zone. The Lagrangian method tracked the particle trajectories to model the particle motion, but the Eulerian model treated the particle as continuous phase. Two cell models were proposed to simulate the transient particle deposition and the cake layer growth on the filter medium surface for the Lagrangian and Eulerian methods, respectively. The simulated results were validated by the available experimental data. Both of the methods could provide relative accurate results with acceptable error. But the computing speed of Eulerian model was faster than the Lagrangian method. Otherwise, the new developed Eulerian model was used to investigate the effect of dust loading on the optimal design of pleated filter. © 2016 American Association for Aerosol Research